Eksplorasi penerapan reward and punishment aparatur sipil negara dalam upaya meningkatkan kedisiplinan pegawai pemerintah kota Sukabumi: Exploration of the implementation of reward and punishment of state civil apparatus in an effort to improve discipline of Sukabumi City Government Employees - Mutia Rahma; Yana Fajar FY Basori; Dian Purwanti (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
The issue of discipline among civil servants is considered one of the bureaucratic pathologies. This can hinder the progress and effectiveness of government, leading to delays in decision-making and a lack of accountability. In the government of Sukabumi City, there are still civil servants who commit violations and social deviations, resulting in disciplinary actions ranging from light to severe, which can cause losses for both the individuals involved and the relevant institutions. The Regional Personnel and Human Resource Development Agency (BKPSDM) of Sukabumi City has implemented a reward and punishment system in an effort to improve employee discipline. This study aims to explore the extent to which the application of reward and punishment impacts the improvement of employee discipline in the Sukabumi City government. The method used is a descriptive research approach with a qualitative perspective, employing instruments such as observation, interviews, and documentation. The results of this study indicate that the implementation of the reward and punishment system in the Sukabumi City government has been effective and has had a positive impact on employee discipline. However, a lack of firmness, transparency, and guidance from leaders has resulted in a weak response from employees towards the reward and punishment system. In addition to the reward and punishment system, the Sukabumi City government also conducts training and technical guidance activities for its employees, aimed at developing human resources and enhancing employee competencies.